2022
DOI: 10.3389/fmed.2022.931867
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Biopsy in Prostate Cancer Patients: Results From an Injection Technique Targeting the Index Lesion in the Prostate Gland

Abstract: ObjectivesTo determine the accuracy of nodal staging in patients with prostate cancer (PCa) when 99mTc-nanocolloid radiotracer is injected into an index lesion (IL).MethodsThis prospective study was conducted at our institution between June 2016 and October 2020. It included 64 patients with localized PCa with at least a 5% possibility for lymph node involvement in the Memorial Sloan Kettering Cancer Center nomogram, suitable for surgical treatment. All patients underwent magnetic resonance imaging (MRI) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The false-negative (FN) rate was 5.5%, whereby one patient had nodal metastasis, despite negative SLNs. Moreover, only 10 of 18 patients (55.6%) had metastasis to SLNs only [80]. Some studies showed similar results, indicating high accuracy rates, but many of them also revealed low detection rates of all metastatic LNs, preventing the application of SLND only [102][103][104][105][106][107].…”
Section: Prostate Cancermentioning
confidence: 91%
See 1 more Smart Citation
“…The false-negative (FN) rate was 5.5%, whereby one patient had nodal metastasis, despite negative SLNs. Moreover, only 10 of 18 patients (55.6%) had metastasis to SLNs only [80]. Some studies showed similar results, indicating high accuracy rates, but many of them also revealed low detection rates of all metastatic LNs, preventing the application of SLND only [102][103][104][105][106][107].…”
Section: Prostate Cancermentioning
confidence: 91%
“…SLNB in PCa was first described by Wawroschek et al in 1999, and then investigated by the same group, as well as Rudoni et al [77][78][79]. Now, almost 25 years later, SLNB is still considered an experimental procedure in PCa [80].…”
Section: Prostate Cancermentioning
confidence: 93%
“…Data collected from the included manuscripts accounted for a total of 2586 patients. Regarding SLN tracer selection, a total of 10 papers reported the use of technetium 99m-nanocolloids (99mTc-NC) [18,19,29,33,35,[37][38][39][40][41], 6 papers of "free" indocyanine green (ICG) [17,22,28,30,32,44], 3 papers of "hybrid" ICG-99mTC-NC tracer [23,24,31], 4 papers superparamagnetic of iron oxide nanoparticles (SPION) [25][26][27]36], 2 papers of PSMA radiotracer [20,21], 1 paper of technetium 99m-sulfur [34], 1 paper of technetium 99mphylate [42], and 1 paper of technetium 99m human serum albumine (HAS) [43]. Two groups combined the use of 99mTc-NC and intraoperative ICG within the same cohort [23,24].…”
Section: Diagnostic Outcomesmentioning
confidence: 99%
“…Two groups combined the use of 99mTc-NC and intraoperative ICG within the same cohort [23,24]. Regarding tracer administration, 11 papers reported an intraprostatic injection template [17][18][19]22,24,25,27,29,37,38,43]. Intra-/peri-lesional administration was performed in two reports [18,29].…”
Section: Diagnostic Outcomesmentioning
confidence: 99%
See 1 more Smart Citation